THE INFLUENCE OF CAPITAL ADEQUACY AND LOAN TO DEPOSIT RATIO ON FINANCIAL PERFORMANCE WITH CREDIT RISK AS A MODERATION VARIABLE IN LISTED BANKING COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Henry Jirwanto (PT. MITRA ANGKASA INFORMATIKA, 2024)
The purpose of this study was to determine and analyze the effect of capital adequacy and loan to deposit ratio on financial performance with credit risk as a moderating variable in banking companies listed on the Indonesia Stock Exchange. A population of 43 banking companies are listed on the Indonesia Stock Exchange for the 2015-2019 period. The research sample was 115 banking companies listed on the Indonesia stock exchange for the period 2015-2019. Researchers used documentation study data collection techniques to collect this research data. The data analysis model used in this study was to use an interaction method which is often referred to as Moderated Regression Analysis (MRA). The results show that capital adequacy has an effect on financial performance in banking companies listed on the Indonesia Stock Exchange. Loan to deposit ratio has no effect on financial performance in banking companies listed on the Indonesia Stock Exchange. The existence of credit risk (moderating variable) will be able to strengthen the relationship between capital adequacy and financial performance. The existence of credit risk (moderating variable) will be able to strengthen the relationship between the loan to deposit ratio and financial performance. The existence of credit risk (moderating variable) will be able to strengthen capital adequacy and loan to deposit ratio on financial performance. Keywords: Capital Adequacy, Loan to Deposit Ratio, Financial Performance and Credit Risk.